"I'm Here to Do Business. I'm Not Here to Play Games." Work, Consumption, and Masculinity in Storage Wars. (January 2016) - Rademacher, Mark A.; Kelly, Casey
This essay examines the first season of Storage Wars and suggests the program helps mediate the putative crisis in American masculinity by suggesting that traditional male skills are still essential where knowledge supplants manual labor. We read representations of "men at work" in traditionally "feminine" consumer markets, as a form of masculine recuperation situated within the culture of White male injury. Specifically, Storage Wars appropriates omnivorous consumption, thrift, and collaboration to fit within the masculine repertoire of self-reliance, individualism, and competition. Thus, the program adapts hegemonic masculinity by showcasing male auction bidders adeptly performing feminine consumer practices. Whether the feminine is assimilated into the male body or represented as its Other, we contend that the expressions of masculinity in Storage Wars render women obsolete and subjugated in the marketplaces of the 21st-century economy and contribute to the mediation of the contemporary crisis in masculinity.